Preparation, spectroscopic analysis, and biological assessment of heteroleptic Zr(II) and Pd(II) complexes from Otc/Sal mixed ligands - Dev, Rohit Kumar; Sahu, Yuv Raj; Chaudhary, Narendra Kumar; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2023)
The two new novel heteroleptic complexes of the type [M(II)L1.L2] (M= Zr(II) & Pd(II), L1= oxytetracycline (Otc), and L2=salicylaldehyde (Sal)) have been synthesized and analyzed by physical measurements such as CHN, pH, and conductivity. The conductivity data revealed the electrolytic nature of Pd(II)Otc/Sal and the non-electrolytic nature of the Zr(II)Otc/Sal metal complex of mixed ligand. The structural characterizations of the metal complex were approved by spectroscopic analysis methods, such as IR, 1H & 13C-NMR, UV/ Visible, and ESI-MS studies. Thermal analysis (TGA/DTA) determines the thermal and kinetic stabilities of the metal complexes using a popular Coats-Redfern equation through which the activation parameters can be calculated easily. SEM can determine the surface morphology of metal complexes. The selected bond lengths, bond angles, final optimized energy, and geometry of complexes were obtained by running an optimization task in the 3D molecular modeling software program via Chem 3D Pro. 12.0.2. The final geometrical energy was found to be 921.7712 for Zr(II)Otc/Sal and 914.6006 Kcal/mol for Pd(II)Otc/Sal complexes. Based on the above study, Zr(II)Otc/Sal complex has tetrahedral geometry and the Pd(II)Otc/Sal complex has square planar geometry. The complexes were tested in vitro for antibacterial susceptibility study against various strains of clinical pathogenic bacteria such as Staphylococcus aureus (Gram-positive), Proteus mirabilis, and Escherichia coli (Gram-negative). For the antibacterial study, the Kirby-Bauer paper disc diffusion technique is applied by using 50, 25, and 12.5 μg/μL concentrations of the metal complex. Good antibacterial sensitivity was found against all tested pathogens in all synthesized complexes.